2008
DOI: 10.1038/ijo.2008.145
|View full text |Cite
|
Sign up to set email alerts
|

Urinary sucrose and fructose as biomarkers of sugar consumption: comparison of normal weight and obese volunteers

Abstract: Using urinary sugars as a biomarker of consumption, we have previously shown that obese people consume significantly more sugars than individuals of normal weight. However, there is concern that recovery of this biomarker may differ between normal weight and obese individuals. A total of 19 subjects, divided into two groups according to their body mass index (BMI) (normal weight BMIp25 kg/m 2 , n ¼ 10; obese BMIX30 kg/m 2 , n ¼ 9), participated in a randomized crossover dietary intervention study of three diet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
5

Year Published

2009
2009
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 16 publications
(16 reference statements)
2
39
5
Order By: Relevance
“…This is also indirectly confirmed by our preliminary diet experiment in adults, which shows a consistent dose response to the ingested amount of fructose administered in the form of sucrose. In this diet experiment, the urinary sucrose excretion failed to turn out as a clear biomarker for sugar consumption, which is somewhat in contrast to the suggestions of other authors, who concluded that both sucrose and fructose are excreted in the urine proportionally to dietary intake (Luceri et al, 1996;Tasevska et al, 2005Tasevska et al, , 2009Joosen et al, 2008). However, in some of these studies, either a higher intraindividual variation (Tasevska et al, 2005) or a less consistent association (Luceri et al, 1996) was seen for urinary sucrose compared with fructose.…”
Section: Discussioncontrasting
confidence: 54%
“…This is also indirectly confirmed by our preliminary diet experiment in adults, which shows a consistent dose response to the ingested amount of fructose administered in the form of sucrose. In this diet experiment, the urinary sucrose excretion failed to turn out as a clear biomarker for sugar consumption, which is somewhat in contrast to the suggestions of other authors, who concluded that both sucrose and fructose are excreted in the urine proportionally to dietary intake (Luceri et al, 1996;Tasevska et al, 2005Tasevska et al, , 2009Joosen et al, 2008). However, in some of these studies, either a higher intraindividual variation (Tasevska et al, 2005) or a less consistent association (Luceri et al, 1996) was seen for urinary sucrose compared with fructose.…”
Section: Discussioncontrasting
confidence: 54%
“…The sucrose measured in urine is derived from dietary sucrose that has escaped enzymatic hydrolysis in the small intestine and is excreted from the general circulation, while the fructose in the urine represents a small fraction of dietary fructose and fructose derived endogenously from hepatic metabolism of sucrose (Tasevska et al 2008). Results from subjects housed in metabolic suites and fed controlled diets suggest that BMI does not aVect the validity of urinary sugars as a biomarker of sugar intake (Joosen et al 2008), which is not well estimated from dietary assessments in obese individuals ). Thus, these predictive biomarkers may be utilized for the purposes of dietary questionnaire validation or as biomarkers of exposure in the overall population.…”
Section: Biomarkers Of Energy Energy Yielding Nutrients and Dietary mentioning
confidence: 97%
“…Joosen et al subsequently determined that body mass index does not influence the association between dietary sugar intake and urinary sucrose levels [370].…”
Section: Iiid Sample Selectionmentioning
confidence: 99%